2017
DOI: 10.1016/j.trsl.2016.06.010
|View full text |Cite
|
Sign up to set email alerts
|

The infant gut bacterial microbiota and risk of pediatric asthma and allergic diseases

Abstract: Among the many areas being revolutionized by the recent introduction of culture independent microbial identification techniques is investigation of the relationship between close contact with large animals, antibiotics, breast feeding, mode of birth, and other exposures during infancy as related to a reduced risk of asthma and allergic disease. These exposures were originally clustered under the “Hygiene Hypothesis” which has morphed into the “Microbiota Hypothesis”. This review begins by summarizing epidemiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
95
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(100 citation statements)
references
References 124 publications
2
95
1
2
Order By: Relevance
“…These results should be viewed as further evidence in support of the evolving “Microbiota Hypothesis” related to allergy and asthma risk . The hypothesis is that the environmental microbial diversity influences the assemblage process of an infant's gut microbiota ecosystem which subsequently, in partnership with exposure to allergens and microbes, influences the child's immune development and risk for allergies and asthma . Evidence supporting this hypothesis continues to increase.…”
Section: Discussionmentioning
confidence: 74%
“…These results should be viewed as further evidence in support of the evolving “Microbiota Hypothesis” related to allergy and asthma risk . The hypothesis is that the environmental microbial diversity influences the assemblage process of an infant's gut microbiota ecosystem which subsequently, in partnership with exposure to allergens and microbes, influences the child's immune development and risk for allergies and asthma . Evidence supporting this hypothesis continues to increase.…”
Section: Discussionmentioning
confidence: 74%
“…During development, the “Hygiene Hypothesis” states that newborns that are delivered by caesarian section or raised in an overly clean environment are more susceptible to pediatric asthma and allergic diseases. Epidemiologic studies have suggested that the common feature of the increases risk of allergy is at least partially due to the perturbation in the founding and early development of a child’s gut microbiota (125). Conversely, allergic airway inflammation can reduce gut microbial diversity, whereas D-tryptophan produced from probiotic supplement does the opposite (126).…”
Section: Gut Microbiota and Liver Diseasesmentioning
confidence: 99%
“…Culture-independent high-throughput methods have revolutionized the identification and quantification of genetic material, and knowledge has rapidly accumulated regarding the microbial composition of human living environments and bodies [68*,69]. These developments occurred concomitantly with the proposal and evolution of the “hygiene hypothesis,” which posits that reduced microbial exposure accounts for the rising prevalence of allergic disease [70].…”
Section: Potential Benefit Of Immunostimulant Microbial Exposuresmentioning
confidence: 99%
“…The hygiene hypothesis is based on the now well-documented finding that risk of allergic disease is reduced in association with a variety of environmental exposures, among which household size was the first to be identified [68*,69,70]. Wu and colleagues recently showed that exposures in early infancy may be particularly important [71*].…”
Section: Potential Benefit Of Immunostimulant Microbial Exposuresmentioning
confidence: 99%
See 1 more Smart Citation